Effect of Characteristics Individuals and Environmental Working to Performance Employees BPN West Aceh - Agus Nureli Nirha (Ridwan Institute, 2021)
This is the lesson was conducted to find out whether Personal characteristics and workplace environment affect employee efficiency in West Aceh District Land Office. All employees at the Land Office of West Aceh Regency are the population, and the sample tested is 37 respondents. This study applies a questionnaire or questionnaire method for data collection. The data collection method multiple linear regression analysis, determinant coefficient (R2), t test, and F test which will be processed with SPSS version 20. Results of the research conclude: Individual Characteristics variable has a significant and positive influence related to employee performance number of b1 = 0.843, the number of t count = 4,800 and significant = 0.000. Employee performance is positively and significantly influenced by the work environment total b2 = 0.318, total t count = 3.510 and significant = 0.001 Personal characteristics and also. The work environment has a positive and significant impact on employee performance at the same time and the number of F count = 53.255 significant amount = 0.000 and the adjusted R2 value is 0.744. Meaning 74.4% Employee performance is explained by individual characteristics and work environment, and the remaining 25.6% is explained due to other factors not tested in this research.